Factors Affecting Food Security of Pond Farmer Households in Bangil District Pasuruan Regency: Factors Affecting Pond Farmers’ Food Security - Melkisedek, Jacob; Fatahullah, Fatahullah (Agriculture Socio-Economic Department, Faculty of Agriculture, Brawijaya University, 2025)
Background and purpose – Food security in Indonesia faces challenges, particularly in East Java's coastal areas like Bangil, where pond farmer households are vulnerable due to poverty, traditional farming practices, and climate change impacts. This study aims to analyze the food security status of pond farmer households in Bangil District, Pasuruan Regency, and the factors influencing it. Methodology – The study was conducted among pond farmers in Bangil District using a survey method. Food security levels were measured using Food Insecurity Experience Scale, while the factors affecting food security was analyzed using Probit. Findings – The results show that the majority of pond farmer households are at a food secure. Factors that affect the food security of pond farmer households are education, pond area, household income, and market access. Implications – The Government should focus increasing access to education, assistance in the form of input and training programs, helping pond farmers to increase their income such as business diversification, and increase access to market.